Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson, 2015)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

The Power of RTI and Reading Profiles: A Blueprint for Solving Reading Problems - Spear-Swerling, Louise (Paul H. Brookes Publishing Co., 2015)
"The reading problems addressed in the book move beyond those associated with disabilities such as dyslexia or high-functioning autism. The author addresses experientially based reading difficulties caused by inadequate instruction or limited exposure to academic language/literacy. Unlike other books on response to intervention (RTI), this book presents an argument for using RTI as a method of identification as well as intervention in combination with individual students' reading profiles. The case studies and practical examples cover a broad range of reading problems (not only learning disabilities) to help make research findings applicable to a multidisciplinary audience, especially practitioners"–
Keywords: Reading disability; Reading; Remedial teaching; Response to intervention (Learning disabled children); dept.sed; faculty_collection

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
1 citations (Crossref) [2023-10-31] tex.eissn: 1936-2706 tex.unique-id: ISI:000363658800011 Citation Key Alias: ISI:000363658800007
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features